2022
DOI: 10.3390/rs14030580
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Urban Land Mappings and Their Distribution with Physical Medium Environments Using Time Series of Land Resource Images in Beijing, China (1981–2021)

Abstract: Rapid urban expansion and structural changes are taking place in China’s capital city, Beijing, but without an update of urban land features in a timely manner our understanding of the new urban heterogeneity is restricted, as land-background data is indispensable for bio-geophysical and bio-geochemical processes. In this plain region, the investigations of multi-scale urban land mappings and physical medium environmental elements such as slope, aspect, and water resource services are still lacking, although B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, the ISA comparison of our study city with a higher-level city (i.e., Beijing, one of the six highest-level cities, the capital city and political, economic, and external centre of China) was conducted in Northern China. The ISA ratio was 65.9% in 1981 and 73.9% in 2021 [46], showing an annual average increment rate of 0.2% from 1981 to 2021, which accounted for only half of the ISA growth rate in our research area. This may be due to the high ratio of ISA in Beijing in 1981 [46], which was higher than that of our study area (i.e., 65.9% in 1981 in Beijing vs. 63.3% in 2000 in Qingdao), and the further increment of ISA space was limited in Beijing, considering the impact of retaining a portion of residential green environment land within the built-up area [46,47].…”
Section: Differences In Characteristic Patterns Of Urban Impervious S...mentioning
confidence: 70%
See 2 more Smart Citations
“…Furthermore, the ISA comparison of our study city with a higher-level city (i.e., Beijing, one of the six highest-level cities, the capital city and political, economic, and external centre of China) was conducted in Northern China. The ISA ratio was 65.9% in 1981 and 73.9% in 2021 [46], showing an annual average increment rate of 0.2% from 1981 to 2021, which accounted for only half of the ISA growth rate in our research area. This may be due to the high ratio of ISA in Beijing in 1981 [46], which was higher than that of our study area (i.e., 65.9% in 1981 in Beijing vs. 63.3% in 2000 in Qingdao), and the further increment of ISA space was limited in Beijing, considering the impact of retaining a portion of residential green environment land within the built-up area [46,47].…”
Section: Differences In Characteristic Patterns Of Urban Impervious S...mentioning
confidence: 70%
“…The findings showed that the response values of the LST to the ISA in the urban regions were higher than those in the rural regions, both horizontally and vertically; the quantitative values were provided for this study. In the horizontal direction, the high-density ISA of cities meets the needs of commercial, residential, and public transportation [45,46] for many urban residents, and large areas of ISA often lead to higher temperature aggregation effects compared to rural areas, where the rural boundaries are relatively small and the ISA density is slightly lower [47]. In the vertical direction, the dense high-rise buildings in urban areas have a certain blocking effect on the horizontal air turbulence, causing temperatures to rise more vertically and forming a relatively high heat island effect [9,48].…”
Section: Mechanism Analysis Of Lst Response To Isa Changes In Urban A...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous literature, construction land [61], including urban, rural land, and industrial and mining land, is always treated as bare land, which often leads to the underestimation of the ecosystem service value in Northeast China. In the contexts of large-scale construction land expansion, ecological elastic cities, livable cities, and rural revitalization policies [64,65] have helped to increase the vegetation within the construction land area. Moreover, the impact of construction land on regional ecological functions such as purified environment, biodiversity, and aesthetic landscape, needs the ecosystem value assessment.…”
Section: The Comparison Comes From the Improved Methods In This Study...mentioning
confidence: 99%